PENGEMBANGAN SDM DALAM PENGELOLAAN KEUANGAN DAN INVESTASI SEJAK USIA DINI PADA SISWA SMKN 1 CIRUAS - Ali, Muhammad Nur; Rufiatun, Yayuk; Mukti, Giri; Asumah, Yayu; Nuraini, Siti (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the human resources (HR) capacity of SMKN 1 Ciruas students in financial management and investment from an early age. Low financial literacy among students often results in an inability to manage personal finances and a lack of understanding of the importance of long-term investment. Through this program, the implementation team provides training in the form of counseling, financial planning simulations, and an introduction to simple investment instruments relevant to students. The methods used include interactive lectures, group discussions, and hands-on practice through case studies of daily financial management. The results of the activity show an increase in students' understanding of basic financial concepts, such as recording income and expenses, budgeting, and the principles of safe saving and investing. In addition, students are able to identify types of investments that suit their beginner risk profiles. This program also encourages the development of discipline and financial awareness from school age. Overall, this community service activity is expected to be the first step in developing a young generation that is financially savvy, independent, and ready to face future economic challenges.